2005
DOI: 10.1002/ijc.21235
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of the putative zinc transporter LIV‐1 are associated with a better outcome of breast cancer patients

Abstract: We investigated the expression pattern of the breast cancer associated gene LIV‐1 on mRNA and protein level in 111 human breast cancer patients by in situ hybridization as well as immunohistochemistry and focused on the unknown potential of LIV‐1 expression levels as a prognostic marker. To our knowledge, this is the first study on endogenous LIV‐1 protein expression. Results of our study indicate that LIV‐1 mRNA and protein expression levels are only weakly correlated, suggesting posttranscriptional regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 43 publications
7
76
0
Order By: Relevance
“…LIV-1 has been demonstrated to be correlated positively with ER expression and negatively with histological grade . Corroborating the data presented here, LIV-1 has also been demonstrated to predict longer relapse-free survival and OS in ER þ breast cancer (Kasper et al, 2005). The same study indicated that the predictive value of LIV-1 is dependent on other prognostic markers.…”
Section: Discussionsupporting
confidence: 82%
“…LIV-1 has been demonstrated to be correlated positively with ER expression and negatively with histological grade . Corroborating the data presented here, LIV-1 has also been demonstrated to predict longer relapse-free survival and OS in ER þ breast cancer (Kasper et al, 2005). The same study indicated that the predictive value of LIV-1 is dependent on other prognostic markers.…”
Section: Discussionsupporting
confidence: 82%
“…Consistently, LIV-1 was expressed higher in carcinoma than in normal tissues and knockdown of LIV-1 by siRNA suppressed cell invasion in cervical carcinoma, suggesting the tumor promoting effect of this gene (12). In contrast, negative association of LIV-1 protein level with tumor size, grade and stage was reported in breast carcinoma tissues (18). In * P<0.05 (B) LIV-1 down-regulated cells (P11 and P18) showed ~40 to 60% reduction of proliferation after 48 h of culture with normal medium and 65 to 75% reduction after 72 h compared to P-EV cells.…”
Section: Discussionmentioning
confidence: 68%
“…Zip6 is thought to be a prognostic indicator of estrogen receptorpositive (ER + ) breast cancer (Kasper et al , 2005 ). Interestingly, Zip6 protein levels are negatively associated with tumor grade, level, and size (Kasper et al , 2005 ). Consistent with this observation, Zip6 attenuation in ER + breast cancer cell …”
Section: Mammary Glandmentioning
confidence: 72%
“…(Shen et al , 2009 ;Lopez and Kelleher , 2010 ), increases mitochondrial membrane potential, and decreases apoptosis (Lopez and Kelleher , 2010 ). This functionally implicates Zip6 in mobilizing Zn 2 + from the endoplasmic reticulum (Taylor and Nicholson , 2003 ;Kasper et al , 2005 ) and modulating mechanisms that restrict epithelial-to-mesenchymal transition (EMT). Zip7 is localized to the endoplasmic reticulum where it functions to increase the mobilization of Zn 2 + into the cytoplasm (Hogstrand et al , 2009 ).…”
Section: Zip12mentioning
confidence: 99%
See 1 more Smart Citation